2011
DOI: 10.1063/1.3651082
|View full text |Cite
|
Sign up to set email alerts
|

Auger decay of molecular double core-hole state

Abstract: 1We report on theoretical Auger electron kinetic energy distribution originated from sequential two-step Auger decays of molecular double core-hole (DCH) state, using CH 4 , NH 3 and H 2 CO molecules as representative examples. For CH 4 and NH 3 molecules, the DCH state has an empty 1s inner-shell orbital and its Auger spectrum has two well separated components. One is originated from the 1st Auger transition from the DCH state to the triply ionized states with one core hole and two valence holes (CVV states) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…However, only the features at 350 eV and 420 eV can be ascribed to Auger transitions, while the structure at higher energies is apparently due to accidental coincidences involving scattered electrons present in the spectrometer and, most likely, electrons from the O1s −1 normal Auger process. The present calculations and those made previously for NH 3 , 12 both predict kinetic energies around 350 eV and 420 eV for Auger electrons from N1s −2 states. The spectrum calculated in the present study, and shown along with the experimental data in Fig.…”
Section: The N 2 O Moleculementioning
confidence: 83%
See 4 more Smart Citations
“…However, only the features at 350 eV and 420 eV can be ascribed to Auger transitions, while the structure at higher energies is apparently due to accidental coincidences involving scattered electrons present in the spectrometer and, most likely, electrons from the O1s −1 normal Auger process. The present calculations and those made previously for NH 3 , 12 both predict kinetic energies around 350 eV and 420 eV for Auger electrons from N1s −2 states. The spectrum calculated in the present study, and shown along with the experimental data in Fig.…”
Section: The N 2 O Moleculementioning
confidence: 83%
“…The two-electron integrals involving the Auger electron orbital were approximated using the population of MOs. 12,20 Further details of the calculation procedure are described in Ref. 12.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations